Legal Analysis of the Prevention and Prosecution of Child Pornography Crimes in the Digital Era - Payu, Siti Rahma (Universitas Pahlawan Tuanku Tambusai, 2025)
A number of technical advancements have come with the digital age, making life simpler for everyone but also increasing the likelihood of criminality, such as child pornography. In addition to harming public morality, sexually exploiting minors is a violation of their human rights. It is the intention of this research to examine, from a legal standpoint, the current state of child pornography prevention and prosecution initiatives in Indonesia. This research uses the normative legal approach to investigate emerging legal concerns and review pertinent statutes and regulations, including those pertaining to electronic information and transactions, child protection, and pornography. Despite the availability of legislation, the research found that significant hurdles such as online anonymity, fast technology advancements, and inadequate law enforcement continue to be prominent issues. For this study to be useful in safeguarding children from online pornography, it is important to improve community digital literacy, tighten the legal framework, and make the most of law enforcement's role